2011
DOI: 10.1111/j.1095-8312.2011.01729.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological benefits of nectar feeding by a predatory beetle

Abstract: Extrafloral nectar is an important food source for many animals, including predatory lady beetles (Coleoptera: Coccinellidae), although the physiological benefits of nectar consumption are poorly understood for most consumers. Under laboratory conditions, we confined new females of Coleomegilla maculata, a North American lady beetle, to Vicia faba plants with or without extrafloral nectaries for 10 days; after this, the beetles were moved onto a high-quality diet for an additional 15 days. Survival, fecundity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 56 publications
1
16
0
1
Order By: Relevance
“…We also observed a positive correlation between the number of predators and legume cover. This supports existing evidence that consuming flowers and extrafloral nectaries improves the survival and nutrient reserves of predators during periods of prey scarcity, and that the availability of nectar during these periods improves the long-term reproductive capacity of predators (Hodek and Honek 1996;Norris and Kogan 2000;Isaacs et al 2009;Lundgren and Seagraves 2011;Amaral et al 2013).…”
Section: Secondary Consumerssupporting
confidence: 87%
“…We also observed a positive correlation between the number of predators and legume cover. This supports existing evidence that consuming flowers and extrafloral nectaries improves the survival and nutrient reserves of predators during periods of prey scarcity, and that the availability of nectar during these periods improves the long-term reproductive capacity of predators (Hodek and Honek 1996;Norris and Kogan 2000;Isaacs et al 2009;Lundgren and Seagraves 2011;Amaral et al 2013).…”
Section: Secondary Consumerssupporting
confidence: 87%
“…In contrast, covering the pollen and nectar sources did not produce different levels of glycogen or lipids in the bugs. Other recent work, however, has shown that while access to nectar greatly improved the levels of glycogen in a predatory beetle, the lipid contents were similar when they were compared with no access to nectar (Lundgren & Seagraves, ). Access to sugar sources also increased the glycogen levels, but not the lipids on a female parasitoid species when it was compared with starved insects (Olson et al., ).…”
Section: Discussionmentioning
confidence: 83%
“…On the contrary, females on the covered treatments, lacking these nutritional resources may have had more incentive to find or create escape routes from the arena (no corpses were found of the missing individuals, reducing the likelihood of cannibalism in the covered treatment). In many other studies, access to sugar sources has improved the survival of predators (Lundgren & Seagraves, ; Portillo et al., ) and parasitoids (Olson et al., ; Lee et al., ). We found that O. insidiosus females laid more eggs when offered nectar and pollen than when these resources were restricted on three of the four flowering plants, although the greatest benefit of floral resources was observed in chamomile, which had low levels of aphids near the flowers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations